Assessment of electronic health literacy and its association with self-management among gout patients: A cross-sectional study - Jiazhen Qian,; Xinyu Yao,; Ting Liu, (Archives of Rheumatology, 2024)
Objectives: This study aimed to assess electronic health (eHealth) literacy and self-management ability among gout patients in China and analyze their correlation. Patients and methods: A cross-sectional study was conducted on 168 male gout patients (mean age: 44.5±13.8 years, range, 22 to 76 years) using a gout patient self-management assessment scale and the Chinese version of eHealth Literacy Scale between August 2020 and February 2021. The correlation between eHealth literacy and gout self-management was examined. Multivariate regression analysis was conducted to identify the predictors of gout patients’ self-management ability. Results: The scores of eHealth literacy and self-management were 28.56±1.72 and 3.59±0.78, respectively, which were both in the medium level, with the lowest score in the lifestyle management dimension. Pearson’s correlation analysis showed that eHealth literacy was significantly and positively associated with the total score of gout self-management and its four dimensions. Literacy in eHealth (β=0.399, p<0.001, 95% confidence interval [CI]: 0.023-0.069), living with family members (β=0.336, p=0.001, 95% CI: 0.313-1.234), living in an urban area (β=0.312, p=0.005, 95% CI: 0.191- 1.022), and having college or a higher level of education (β=0.268, p=0.016, 95% CI: 0.032-0.302) were the significant predictors of gout patients’ self-management ability, explained 30.6% of the total variance. Conclusion: Literacy in eHealth was the most significant predictor of gout self-management ability. Gout patients had the lowest score in the perceived ability of searching and applying online health-related information, indicating that both the quantity and quality of gout-specific information needs to be enlarged in electronic resources. Healthcare providers could design and implement eHealth literacy interventions to strengthen patients’ gout self-management ability